The effect of Customer Relationship Management (CRM), service quality, and value creation on customer satisfaction among customers of PT. Pegadaian (Persero) Cisalak Branch - Depok - Noviono, Andhi Dwy (Privietlab, 2025)
This study investigates how Customer Relationship Management (CRM), service quality, and value creation shape customer satisfaction in a public pawn-based financial institution. Using a quantitative, cross-sectional survey of 125 customers at PT Pegadaian (Persero) Cisalak Branch (Depok), we operationalize CRM, service quality (SERVQUAL dimensions), value creation (product, price, promotion, place), and satisfaction on five-point Likert scales. Bivariate correlations show all three antecedents are positively and significantly associated with satisfaction (p < 0.01). In multiple regression, the joint model is significant (F = 32.161, p < 0.001) and explains 44.4% of the variance in satisfaction; service quality (β = 0.355, p < 0.001) and value creation (β = 0.327, p < 0.001) retain strong, independent effects, while CRM’s partial effect becomes statistically non-significant when the other predictors are included. Descriptive results highlight consistently favorable perceptions of frontline assistance and pricing/fee structures, with opportunities to improve complaint handling, expectation alignment for appraisal amounts, and reminder practices. The findings imply that satisfaction in this context is won primarily “at the counter” (reliable, responsive, empathetic service) and “at the ledger” (transparent, fair, and flexible economics), with CRM best positioned as an enabling backbone that strengthens execution and tailored communication. Managerially, an integrated program that hardwires service standards, clarifies value propositions, and uses CRM data to personalize outreach is most likely to convert repeat usage intent into durable loyalty.